Design of Waste Processing System in Slum Area by 3R Waste Treatment Site (Case Study: Tangerang City, Indonesia) - Nova Ulhasanah; Rizky Mahlisa; Betanti Ridhosari (Journal of Sustainable Infrastructure, 2023)
This design contains the process of designing a Reduce, Reuse, Recycle (3R) Waste Processing Facility that can handle residential waste in Selapajang Jaya Sub-district. The objective of this design is to create a recommendation for a 3R Waste Processing Facility that complies with the 3R Waste Processing Facility Technical Guidelines and can reduce waste volume before being transported to the Landfill (TPA). Additionally, the design includes a budget plan covering investment costs, operational and maintenance costs, and assumptions about the revenue received by the 3R Waste Processing Facility. There are 3 design alternatives that will be selected using the Utility Theory and Compromise Program methods. The chosen best alternative involves processing organic waste using hollow brick boxes and plastic waste using a shredder machine. This design is capable of handling a waste generation of 22.449 m3/day from 1.952 households in Selapajang Jaya Sub-district. The facility includes waste sorting area, residue storage area, plastic waste processing area, organic waste processing area, warehouse, office, security post, and toilets. Theoretically, this 3R Waste Processing Facility can reduce the amount of waste by 61.17%. The design requires an investment cost of Rp 434,370,815 with a monthly operational and maintenance cost of Rp 45,781,470, and an estimated monthly revenue of Rp 94,148,061 for the 3R Waste Processing Facility.